2022
DOI: 10.1088/2050-6120/ac7d3f
|View full text |Cite
|
Sign up to set email alerts
|

Genetically encodable fluorescent protein markers in advanced optical imaging

Abstract: Optical fluorescence microscopy plays a pivotal role in the exploration of biological structure and dynamics, especially on live specimens. Progress in the field relies, on the one hand, on technical advances in imaging and data processing and, on the other hand, on progress in fluorescent marker technologies. Among these, genetically encodable fluorescent proteins (FPs) are invaluable tools, as they allow facile labeling of live cells, tissues or organisms, as these produce the FP markers all by themselves af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 267 publications
1
19
0
Order By: Relevance
“…Early experimental and theoretical studies of GFP have revealed a complex interplay between a relatively simple chromophore formed after specific biosynthesis, and the spatial and dynamic organization of its protein carrier (Scheme 4). [94,[98][99] Today, through mutation and selection, many GFP variants were designed that differ in protein and chromophore structure, intending to tune their absorbance and emission characteristics. Popular variants of more enhanced and stable GFP were produced, such as cyan, and yellow fluorescent proteins (ECFP, EYFP, etc.).…”
Section: Biosynthetically Incorporated Fluorescent Proteins and Lanth...mentioning
confidence: 99%
See 1 more Smart Citation
“…Early experimental and theoretical studies of GFP have revealed a complex interplay between a relatively simple chromophore formed after specific biosynthesis, and the spatial and dynamic organization of its protein carrier (Scheme 4). [94,[98][99] Today, through mutation and selection, many GFP variants were designed that differ in protein and chromophore structure, intending to tune their absorbance and emission characteristics. Popular variants of more enhanced and stable GFP were produced, such as cyan, and yellow fluorescent proteins (ECFP, EYFP, etc.).…”
Section: Biosynthetically Incorporated Fluorescent Proteins and Lanth...mentioning
confidence: 99%
“…Early experimental and theoretical studies of GFP have revealed a complex interplay between a relatively simple chromophore formed after specific biosynthesis, and the spatial and dynamic organization of its protein carrier (Scheme 4). [94,98–99] …”
Section: Applications Of Intrinsic and Extrinsic Environment‐sensitiv...mentioning
confidence: 99%
“…Other staining approaches include the use of genetically encodable fluorescent proteins. 8 Their signal is sufficiently bright and stable and allows tracking individual cells and molecular parts. However, the gene modification that is required for these proteins’ expression can lead to spontaneous mutation and changes in the properties of cell culture relative to the original, which calls into question the adequacy of data obtained from the transfected culture.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of luminescent nanoparticles [9] can be even more challenging and is driven by advancements in the materials sciences [10] . Fluorescent proteins represent another important type of luminescent reporters that are mainly used for imaging applications [11] …”
Section: Introductionmentioning
confidence: 99%
“…[10] Fluorescent proteins represent another important type of luminescent reporters that are mainly used for imaging applications. [11] Although nanoparticles are larger in size compared to molecular reporters such as fluorescent dyes or lanthanide complexes, they provide several advantages as luminescent labels and probes. For example, luminescent nanoparticles are typically much brighter and more photostable than fluorescent dyes, which are prone to photobleaching by singlet oxygen and thus not suitable for long-time applications under strong illumination.…”
Section: Introductionmentioning
confidence: 99%